Modeling of Wax Crystallization in Production of Lube Oil Base Stock in Solvent Dewaxing - Mukhlif, Nassir D. (2011)
A mathematical model of a steady heat transfer and crystallization was established in double pipe scraped surface heat exchangers and chillers for solvent dewaxing process. The model equations were numerically solved to obtain, the temperatures distribution, wax volume fraction, crystals number and their size in the wax-oil-solvent solution. The prediction of the physical properties and the nucleation and crystal growth constants based on the adjustable selection of the higher carbon number as a solute and light ones as liquid. The procedure depends on experimental measurements of the carbon number distribution in the feedstock, dissolved temperature, onset crystallization temperature, and the wax content. The measurement results were linked to a solubility model, which attaches the wax content and the dissolving temperature of the feed stock to choose the wax compound. The numerical model results showed that the proposed solubility model give a good estimation of the wax crystals characteristics of such complex process.